2017
DOI: 10.1186/s12872-017-0698-8
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a PRECEDE-based education intervention on quality of life in elderly patients with chronic heart failure

Abstract: BackgroundOne of the most important challenges in public health is to improve the quality of life in patients with chronic heart failure (CHF). Depression, self-care capacity, and quality of life interact each other in these patients. It’s difficult to treat with general education programs and conventional therapy. PRECEDE model is a comprehensive and exclusive theory-based education programs. Its effectiveness for reducing depression and increasing quality of life has been demonstrated in patients with corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 33 publications
2
65
0
9
Order By: Relevance
“…[14]. Wang et al [15] found that education level was positively correlated with patients' abilities to self-manage medication, treatments, and administration of medication, and that higher education levels could facilitate compliance with adaptive healthy behaviours. Hailan et al [16] discovered that males tended to have a greater need for medical help at the onset of CHF than females, that patients in poorer health engaged in fewer activities, and that patients with low incomes had lower levels of self-care ability.…”
Section: Discussionmentioning
confidence: 99%
“…[14]. Wang et al [15] found that education level was positively correlated with patients' abilities to self-manage medication, treatments, and administration of medication, and that higher education levels could facilitate compliance with adaptive healthy behaviours. Hailan et al [16] discovered that males tended to have a greater need for medical help at the onset of CHF than females, that patients in poorer health engaged in fewer activities, and that patients with low incomes had lower levels of self-care ability.…”
Section: Discussionmentioning
confidence: 99%
“…The results of other studies based on PRECEDE-PROCEED model show that this pattern is effective in enhancing life quality. The results of the study by Shore concerning improving life quality in relation to epilepsy [29], the study by Wang et al regarding life quality in the elderly with chronic heart failure [30], as well as the study by Zhu et al on the effect of educational intervention on improving physical health, as one of the dimensions of life quality of immigrant women workers [31] are in this regard. One has to note that the role of educational interventions in improving the life quality in different people, especially chronic diseases like hypertension, should not be ignored.…”
Section: Discussionmentioning
confidence: 90%
“…The self-care theory, rst introduced in 1959 by Dorothea Orem, has been demonstrated to reduce side effects of medical treatments and improve QoL among patients of various diseases [14][15][16]. It contains descriptions regarding the role of the nurse to help individuals who experiences inabilities in self-care.…”
Section: Introductionmentioning
confidence: 99%